The Conflict between Top-down and Bottom-up Impairments in Consciousness Disorder in Schizophrenia - Karbakhsh, Hesam; Kouchakzadeh, Aliakbar; Gharibzadeh, Shahriar (Current Psychiatry Research and Reviews, 2024)
Introduction: Schizophrenia, a complex psychiatric disorder, is often associated with consciousness disorders, typically characterized by an elevated threshold of conscious perception. Over the years, a multitude of research has been dedicated to uncovering the primary cause of these disorders, leading to the development of several theories. Methods: In this article, two central answers to this problem have been reviewed. For this, the articles that were more related to the topic were selected. Based on the relevance to the subject of research, the main ideas of targeted articles are reordered to be comprehensible for the readers. Finally, the judgment and conclusion of the authors about the discussed problem are presented in this study. Discussion: The first theory, which we will explore in this article, suggests that the root cause of these disorders lies in defects within bottom-up processes. These processes, fundamental to our understanding of the world, involve the progression of sensory information from low-level perception to high-level awareness. In individuals with schizophrenia, these processes are believed to be compromised, leading to a distorted perception of reality. The second theory, in contrast, attributes the cause to impairments in top-down processes. These processes, which refer to the influence of high-level cognitive functions on lower-level sensory perception, are also considered dysfunctional in schizophrenic patients. This dysfunction is thought to disrupt the integration of sensory information, thereby affecting the individual's consciousness. However, a third perspective has emerged, suggesting the coexistence of impairments in both bottom- up and top-down processing. This perspective argues that to fully comprehend the nature of consciousness disorders in schizophrenia, it is crucial to determine the type and severity of both bottom-up and top-down impairments. Conclusion: In this review, we delve into these theories, examining the evidence supporting each and discussing their implications for our understanding of schizophrenia. Considering both bottom-up and top-down impairments, the third perspective offers a more holistic explanation for these disorders. We further argue that this perspective underscores the need for a more nuanced approach to studying schizophrenia. It suggests that future research should not only focus on these processes in isolation but also explore their interaction and the potential synergistic effects of their impairment. By doing so, we can hope to gain a more comprehensive understanding of consciousness disorders in schizophrenia, which could ultimately lead to more effective treatment strategies.
Keywords: Consciousness disorder